Bioecological peculiarities of mid-ripening varieties of strawberry (Fragaria ananassa Duch.) in the northern part of the Forest-Steppe zone of Ukraine - В. В. Павлюк; Н. С. Ковальчук; Н. В. Павлюк (Plant Varieties Studying and Protection)
Purpose. Improvement of a range of strawberry varieties based on comprehensive study and introduction of new Ukrainian and West European cultivars. Methods. Cultivars and elite forms were studied using the methods of primary variety studying and state variety testing at three-year strawberry plantations of the Institute of Horticulture of the National Academy of Sciences of Ukraine (the city of Kyiv) and its variety testing stations. Results. It was found that more frequent spring and summer droughts as well as black frosts in winter adversely affected the strawberry productivity. The best varieties were selected among new ones for the complex of traits, they included ‘Elegance’ from the Great Britain, ‘Gercules’ from Ukraine (both are dessert grapes), ‘Elsanta’ from Holland (for universal use), ‘Alba’ from Italia (as raw material). The highly adaptive and productive ‘Istochnik’ and ‘Festyvalna romashka’ varieties (as raw material) are recommended for the north regions. Conclusions. In the context of profound climatic change, high-profitable cultivation of mid-ripening varieties and a strawberry as such in the Northern Forest-Steppe zone is expedient under controlled conditions – in high film tunnels, in hot-houses and under perennial irrigation that already has become the European tendency.